หลักไวยากรณ์ในการกลมกลืนเสียงสัทศาสตร์ในระดับประโยคภาษาอังกฤษ; Writing the Unwritten Grammar of Fluid English Pronunciation: Sentence-level Phonetic Blends in 2017 Spoken English - Flynn, Frederick (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2018)
ภาษาพูดและเขียนภาษาอังกฤษที่แตกต่างกันอย่างมากโดยเฉพาะจากการที่หยุดชะงักเสียงระหว่างวลีต่าง ๆ และลักษณะที่เกิดของเสียงกับเสียงที่ประสมกันเพื่อที่จะกำหนดการเปล่งเสียงเดียวในคำต่าง ๆ เหล่านี้ได้กำหนดขึ้นมากับคำจำนวนมาก แต่อย่างไรก็ตามในการวิเคราะห์กฎการภาษาพูดภาษาอังกฤษทั้งที่พูดแบบอังกฤษและอเมริกันที่เป็นโครงสร้างภาษาพูดโดยได้ถูกค้นพบว่ามีส่วนทำให้การพูดมีความไหลลื่นและคล่องแคล่วตามที่มีกฎเกณฑ์เดียวกันการประสมคำจากสัทอักษรในระดับประโยค (ที่เปล่งเสียงพูด) ได้ถูกนำมาจัดคุณภาพ ให้เป็นกฎการออกเสียงเพื่อที่จะพัฒนาการสอนภาษาอังกฤษแก่ผู้เรียนต่างชาติโดยการใช้เครื่องมือที่เรียกว่าข้อควรระวังสัทอักษรระดับประโยคนอกจากนี้กฎต่างๆที่ค้นพบยังสะท้อนให้เห็นถึงโครงสร้างภาษาพูดและอาจจะมีสาเหตุในส่วนที่มาจากข้อจำกัดทางกายภาพ เช่น ตำแหน่งของลิ้น ตำแหน่งของขากรรไกร และปัจจัยทางกายภาพอื่นที่เป็นสาเหตุกำหนดการเชื่อมต่อเสียงระหว่างสัทอักษรในขณะที่พูด Abstract Spoken and written English diverge greatly, especially in regards to pauses between phrases and also in the manner in which words blend together to form single utterances, each of which can be composed of a great number of words. However, in analyzing English spoken in both the U.K. and U.S.A. a set of rules, a spoken grammar, were found to uniformly contribute to fluid and smooth speech. These sentence-level phonetic blends (utterances) are here quantified as Rules to enhance the teaching of English to foreign learners by using a tool called sentence-level phonetic awareness. Further, these rules reflect spoken grammar, and may be caused in part by physical constraints such as tongue position, jaw position and other physical factors that form transitions between phonemes while speaking.